PERAN MUHAMMADIYAH DALAM PENGEMBANGAN MASYARAKAT AGRARIS DI KABUPATEN BANDUNG - Utan Sahiro Ritonga; Euis Evi Puspitasari (Universitas Sebelas Maret, 2022)
Community welfare is not only the responsibility of the central government but all parties according to their respective roles and functions. Considering that Indonesia is an agricultural country where most population works as farmers in rural areas, attention to developing farmer economic capacity is important in efforts to improve the welfare of the community. Muhammadiyah as a religious-based community organization has carried out its ‘dakwah’ role through the development of agrarian communities in rural areas. This study aims to determine farmers characteristics associated with the level of this role through a quantitative research approach. The testing technique in this study was carried out using three-box method and chi-square Pearson on survey data was collected non-probability with the technique as purposive samples. The results show that Muhammadiyah plays very significant role as a learning class, a forum for cooperation, and a production unit for farmers in Bandung Regency. Farmer's age, education level, length of farming, and income level had positively related, and group experience was negatively related to Muhammadiyah's role as learning class. Education level and length of farming had positive relationship, and farmer's income level had negative relationship with Muhammadiyah roles as production unit. Outstanding roles achievement from group to develop an agrarian society had a relationship with farmer characteristics that should be considered by interested parties for the farmer welfare, to achieve the role of group as an institution following the common ideals and expectations of farmers.